2020
DOI: 10.3390/ijms21145056
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Tissue-Specific Promoter Methylation and Gene Expression Profile in Complex Diseases

Abstract: This study investigated whether the promoter region of DNA methylation positively or negatively regulates tissue-specific genes (TSGs) and if it correlates with disease pathophysiology. We assessed tissue specificity metrics in five human tissues, using sequencing-based approaches, including 52 whole genome bisulfite sequencing (WGBS), 52 RNA-seq, and 144 chromatin immunoprecipitation sequencing (ChIP-seq) data. A correlation analysis was performed between the gene expression and DNA methylation levels of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Amongst the 23 papers included in this systematic review, 19 papers reported studies on DNA methylation, 2 papers presented data on histone modifications and 2 papers conducted studies on lncRNAs. Of the 19 papers that reported data on DNA methylation in AT from individuals with MUHO, 8 papers performed targeted epigenome studies (52-59) and 11 papers reported genome-wide studies (60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). The main findings on the targeted DNA methylation studies are summarized in Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…Amongst the 23 papers included in this systematic review, 19 papers reported studies on DNA methylation, 2 papers presented data on histone modifications and 2 papers conducted studies on lncRNAs. Of the 19 papers that reported data on DNA methylation in AT from individuals with MUHO, 8 papers performed targeted epigenome studies (52-59) and 11 papers reported genome-wide studies (60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). The main findings on the targeted DNA methylation studies are summarized in Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…As only SOX7 had a significant correlation between CNV and its expression, we continued to explore factors that may affect the expression of SOX17 and SOX18 from other perspectives. It has been reported that the methylation of the promoter region can affect the expression of genes (37). Therefore, we explored the methylation of SOXF family genes.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SOX17 is more affected by the level of methylation, but the factors affecting the changes in SOX18 expression still need to be explored. It has been reported that the methylation of the promoter region of the RASSF1 gene can be used as an effective biomarker for the early diagnosis of lung cancer (37). To explore whether SOXF family genes have similar capabilities, we compared SOXF family genes with RASSF1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene mutation and methylation can regulate gene expression ( 23 , 24 ). The study demonstrated that the incidence of SNV mutations was very low.…”
Section: Discussionmentioning
confidence: 99%